Unveiling tumor immune evasion mechanisms: abnormal expression of transporters on immune cells in the tumor microenvironment - Chen, Lu; Wang, Yuchen; Hu, Qingqing; Liu, Yuxi; Qi, Xuchen; Tang, Zhihua; Hu, Haihong; Lin, Nengming; Zeng, Su; Yu, Lushan (Frontiers in Immunology, 2023)
The tumor microenvironment (TME) is a crucial driving factor for tumor progression and it can hinder the body’s immune response by altering the metabolic activity of immune cells. Both tumor and immune cells maintain their proliferative characteristics and physiological functions through transporter-mediated regulation of nutrient acquisition and metabolite efflux. Transporters also play an important role in modulating immune responses in the TME. In this review, we outline the metabolic characteristics of the TME and systematically elaborate on the effects of abundant metabolites on immune cell function and transporter expression. We also discuss the mechanism of tumor immune escape due to transporter dysfunction. Finally, we introduce some transporter-targeted antitumor therapeutic strategies, with the aim of providing new insights into the development of antitumor drugs and rational drug usage for clinical cancer therapy.